Malaria case-management following change of policy to universal parasitological diagnosis and targeted artemisinin-based combination therapy in Kenya. - Nyandigisi, A; Memusi, D; Mbithi, A; Ang'wa, N; Shieshia, M; Muturi, A; Sudoi, R; Githinji, S; Juma, E; Zurovac, D (Public Library of Science, 2011)
BACKGROUND: The change of malaria case-management policy in Kenya to recommend universal parasitological diagnosis and targeted treatment with artemether-lumefantrine (AL) is supported with activities aiming by 2013 at universal coverage and adherence to the recommendations. We evaluated changes in health systems and case-management indicators between the baseline survey undertaken before implementation of the policy and the follow-up survey following the first year of the implementation activities. METHODS/FINDINGS: National, cross-sectional surveys using quality-of-care methods were undertaken at public facilities. Baseline and follow-up surveys respectively included 174 and 176 facilities, 224 and 237 health workers, and 2,405 and 1,456 febrile patients. Health systems indicators showed variable changes between surveys: AL stock-out (27% to 21%; p = 0.152); availability of diagnostics (55% to 58%; p = 0.600); training on the new policy (0 to 22%; p = 0.001); exposure to supervision (18% to 13%; p = 0.156) and access to guidelines (0 to 6%; p = 0.001). At all facilities, there was an increase among patients tested for malaria (24% vs 31%; p = 0.090) and those who were both tested and treated according to test result (16% to 22%; p = 0.048). At facilities with AL and malaria diagnostics, testing increased from 43% to 50% (p = 0.196) while patients who were both, tested and treated according to test result, increased from 28% to 36% (p = 0.114). Treatment adherence improved for test positive patients from 83% to 90% (p = 0.150) and for test negative patients from 47% to 56% (p = 0.227). No association was found between testing and exposure to training, supervision and guidelines, however, testing was significantly associated with facility ownership, type of testing, and patients' caseload, age and clinical presentation. CONCLUSIONS: Most of the case-management indicators have shown some improvement trends; however differences were smaller than expected, rarely statistically significant and still leaving a substantial gap towards optimistic targets. The quantitative and qualitative improvement of interventions will ultimately determine the success of the new policy.